Solar and geomagnetic activity control on equatorial VHF Scintillations in the Indian region - Banola, S.; Maurya, R.N.; Chandra, H. (My University, 2010)
A network of stations was operated monitoring amplitude scintillations of 244/251 MHz signal from FLEETSAT (73º E) in India for over a solar cycle. Latitudinal width of the equatorial belt of scintillation is higher during D-months and E-months compared to J-months. There is a positive correlation between the width of the belt and solar activity. Width of the belt decreases with magnetic activity. Equatorial scintillations are inhibited during magnetic disturbances with seasonal and solar cycle dependence. An analysis covering more than 200 geomagnetic storm events show scintillations at low latitudes can be either inhibited or triggered during storms depending on the phase of the storm and local time of occurrence.
Keywords: Solar activity; Geomagnetic activity; VHF; Scintillations; Storms